Early Active Mobilization of Mechanically Ventilated Patients in the ICU: A Qualitative Study on Patient Experience - Xiaomeng Han MSc; Qian Wang MSc; Hengyang Wang MSc; Donghui Jia MSc; Jie Cheng MSc; Rui Wang MSc; Caiyun Zhang MD; Jiajia Kong MSc; Zhigang Zhang MD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
This study aims to explore the experiences of mechanically ventilated ICU patients receiving early active mobilization, with a focus on their perceptions, emotions, and psychological impacts to inform nursing practices. A qualitative approach using semi-structured interviews and thematic content analysis was employed, with interviews conducted face-to-face between March and December 2021 across 5 comprehensive hospitals. Data from 14 patients were analyzed using Colaizzi’s 7-step method, revealing 3 main themes: (1) Significant physical discomfort, including feelings of weakness, foreign body sensation, pain, and fatigue; (2) Complex psychological experiences, with perceived benefits, negative self-perception, and diverse emotional responses; and (3) Expectations for treatment, such as a desire for family support, rehabilitation goals, and humanized care. The study found that mechanically ventilated ICU patients undergoing early active mobilization experienced significant physical discomfort, complex psychological responses, and had specific expectations for treatment, highlighting the need for holistic nursing practices that address these aspects.